2010
DOI: 10.1097/meg.0b013e32833f71f6
|View full text |Cite
|
Sign up to set email alerts
|

Human kidney histopathology in acute obstructive jaundice

Abstract: This study is the first in the literature to address the histopathological changes that occur in humans with short-term biliary obstruction. Acute tubular necrosis and venous dilatation was observed in all biopsies, without exception, despite the maintenance of strict volume control in all patients. The adequacy of volume control may not be implicated in those results; rather a possible mechanism related to untrapped endotoxin in the gut lumen or systemic circulation might lead to prolonged PTC dilatation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(30 citation statements)
references
References 28 publications
0
28
1
1
Order By: Relevance
“…fulminant AIH). Interestingly, and in contrast to the study by Uslu et al [73], the presence of bile casts in these patients significantly correlated with the degree of jaundice (total and direct bilirubin levels). It is important to note that 13 of 44 patients in the study were clinically classified as having HRS; however, 11 (85%) out of these 13 patients showed bile casts upon kidney histology.…”
Section: Recent Clinical Evidence For Cncontrasting
confidence: 53%
See 2 more Smart Citations
“…fulminant AIH). Interestingly, and in contrast to the study by Uslu et al [73], the presence of bile casts in these patients significantly correlated with the degree of jaundice (total and direct bilirubin levels). It is important to note that 13 of 44 patients in the study were clinically classified as having HRS; however, 11 (85%) out of these 13 patients showed bile casts upon kidney histology.…”
Section: Recent Clinical Evidence For Cncontrasting
confidence: 53%
“…As such, Uslu et al [73] published a prospective study in 20 patients with short-term obstructive jaundice (mean duration of biliary obstruction of 15 days, mean total bilirubin: 10.1 ± 1.0 mg/dl), and demonstrated that those patients frequently showed acute tubular necrosis and venous dilatation upon renal biopsies despite maintenance of strict perioperative volume control and normal to only slightly impaired renal function (preoperative serum creatinine: 0.97 ± 0.1 mg/dl, mean GFR determined by MDRD equation: 81.9 ± 0.4 ml/min). Their study did not show a correlation between severity of jaundice (total bilirubin levels) and severity of the tubular and vascular changes observed.…”
Section: Recent Clinical Evidence For Cnmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have shown that multiple organ injury occurs in CC [68]. CC with liver dysfunction is frequently accompanied by kidney injury [912], which could be caused by endotoxemia, vasoactive mediators, and free radicals [1315]. In addition, renal injury associated with liver diseases could occur by direct tubular toxicity or nephron obstruction [16].…”
Section: Introductionmentioning
confidence: 99%
“…Acute kidney injuries (AKI) in patients with severe jaundice have often been reported 1 2. This has led the medical community to consider cholestasis as a cause of renal failure, and to classify this mechanism of injury under the term, ‘cholemic nephropathy’.…”
Section: Introductionmentioning
confidence: 99%